2000
DOI: 10.1039/b001107j
|View full text |Cite
|
Sign up to set email alerts
|

Poly(aniline)–poly(acrylate) composite films as modified electrodes for the oxidation of NADH

Abstract: Poly(aniline), electrochemically deposited on an electrode surface in the presence of poly(acrylic acid), forms a Ðlm which remains protonated, and conducting, at pH 7. The resulting modiÐed electrode is an electrocatalytic surface for NADH oxidation at ]0.05 V vs. SCE in 0.1 M citrateÈphosphate bu †er at pH 7. The amperometric responses of these composite poly(aniline) Ðlms for NADH oxidation were studied in detail and Ðtted to a kinetic model in which the NADH di †uses into the polymer Ðlm and then binds to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 12 publications
2
76
0
Order By: Relevance
“…The above results are similar to those found for PANI copolymers. [11,12] Figure 4 shows the cyclic voltammograms of 6 bilayers of PANI/SPANI recorded in 0.1 M PBS buffer (pH 7.1) at different scan rates. The inset shows the plot of the anodic peak current versus the square root of the scan rate.…”
Section: Full Papermentioning
confidence: 99%
See 1 more Smart Citation
“…The above results are similar to those found for PANI copolymers. [11,12] Figure 4 shows the cyclic voltammograms of 6 bilayers of PANI/SPANI recorded in 0.1 M PBS buffer (pH 7.1) at different scan rates. The inset shows the plot of the anodic peak current versus the square root of the scan rate.…”
Section: Full Papermentioning
confidence: 99%
“…For PANI copolymers this process was reported to be surface controlled. [12] The difference may arise from the different structures of PANI/SPANI multilayer films and PANI copolymers. The former is more ordered and compact than the latter.…”
Section: Full Papermentioning
confidence: 99%
“…When the oxidation of NADH was conducted using an unmodified GCE, the electrochemical oxidation peak was observed at around + 0.56 V. The decrease in overpotential indicated that the imine group of pAPRu catalyzed the electrochemical oxidation of NADH as a mediator. The potential of pAPRu is comparable to that of other mediators of NADH oxidation, such as poly(aniline)-poly(anion) composites [21][22][23], However, poly(aniline) could not catalyze the electrochemical oxidation of NADH when poly-(aniline) lost its conductivity. To maintain the conductivity, the polymeric counter anion used as a dopant was entrapped within the poly(aniline) film [21,22].…”
Section: Electrochemical Oxidation Of Nadhmentioning
confidence: 88%
“…The potential of pAPRu is comparable to that of other mediators of NADH oxidation, such as poly(aniline)-poly(anion) composites [21][22][23], However, poly(aniline) could not catalyze the electrochemical oxidation of NADH when poly-(aniline) lost its conductivity. To maintain the conductivity, the polymeric counter anion used as a dopant was entrapped within the poly(aniline) film [21,22]. However, the pAPRu/GCE could catalyze the electrochemical oxidation of NADH without doping.…”
Section: Electrochemical Oxidation Of Nadhmentioning
confidence: 88%
See 1 more Smart Citation